Linking cell-surface GRP78 to cancer: From basic research to clinical value of GRP78 antibodies. (1st January 2022) - Hernandez, Isabelle; Cohen, Marie
Abstract: Glucose-related protein 78 (GRP78) is a chaperone protein localized primarily in the endoplasmic reticulum (ER) lumen, where it helps in proper protein folding by targeting misfolded proteins and facilitating protein assembly. In stressed cells, GRP78 is translocated to the cell surface (csGRP78) where it binds to various ligands and triggers different intracellular pathways. Thus, csGRP78 expression is associated with cancer, involved in the maintenance and progression of the disease. Extracellular exposition of csGRP78 leads to the production of autoantibodies as observed in patients with prostate or ovarian cancer, in which the ability to target csGRP78 affects the tumor development. Present on the surface of cancer cells and not normal cells in vivo, csGRP78 represents an interesting target for therapeutic antibody strategies. Here we give an overview of the csGRP78 function in the cell and its role in oncogenesis, thereby providing insight into the clinical value of GRP78 monoclonal antibodies for cancer prognosis and treatment. Highlights: GRP78 is expressed on cancer, trophoblastic and endothelial cell surface. Cell surface GRP78 (csGRP78) leads to the production of GRP78 autoantibodies. GRP78 autoantibody may be used as cancer biomarker. CsGRP78 regulates cancer cell proliferation, migration, invasion, stemness and fate. GRP78 Ab are promising tools to target, kill or modulate cancer cells environment.